The combined effect of decreased stomatal density and aperture increases water use efficiency in maize - Larissa Barl; Betina Debastiani Benato; Nikita Genze; Dominik G. Grimm; Michael Gigl; Corinna Dawid; Chris-Carolin Schön; Viktoriya Avramova (Scientific Reports)
Abstract Stomata play a crucial role in balancing carbon dioxide uptake and water vapor loss, thereby regulating plant water use efficiency (WUE). Enhancing WUE is important for sustainable agriculture and food security, particularly for crops such as maize (Zea mays L.), as climate change and growing global food demand exacerbate limitations on water availability. Genetic factors controlling stomatal density and levels of the plant hormone abscisic acid (ABA) in leaves, which affect stomatal aperture, are key determinants of stomatal conductance (gs) and intrinsic WUE (iWUE). In this study, we demonstrate that stomatal density and stomatal aperture have a combined effect on gs and iWUE in maize. Using near-isogenic lines (NILs) and CRISPR/Cas9 mutants, we show that combining reduced stomatal density and reduced stomatal aperture can improve iWUE without compromising photosynthesis. This effect is pronounced at both, optimal and high temperatures. These findings highlight the potential of targeting multiple stomatal traits through genetic stacking to enhance WUE, offering a promising strategy for crop adaptation to water-limited environments.